Monitoring and analysis of external deformation of face rock-fill dam during initial storage period. Issue 1 (June 2020) - Li, Xiuwen; Wu, Hao; Tian, Dongcheng; Zhang, Shunfu
Abstract: During the initial storage period of the face rock-fill dam, its physical and mechanical properties will not be in a fully controlled state when it is subjected to the test of water loads, which may cause certain safety risks. The stability of the dam body and slope can be analyzed by studying the external deformation changes of the face rock-fill dam after water storage. This article analyzes the external deformation monitoring data of the Hekou Village Reservoir's face rock-fill dam during the initial storage period, and it reveals the general rule of the external deformation of the face rock-fill dam after water storage. The results also show that the dam is safe after storing water and have certain reference significance for other similar projects.